Modern approach to the Design of Museums - Shodieva Mohira Khusanovna; Ochilov Farhod Egamberdievich (International Journal on Human-Computing Studies, 2021)
The article discusses the basic principles of designing modern museums. The goals and objectives of the work on museum projects are also given. Also shown are the successive stages of joint work in the design of museums